Pengembangan Softskill Bagi Kesiapan Alumni Penerima Beasiswa Non Gelar Mosma 2023 Kementrian Agama - Anggriani, Irien Violinda; Rahmadani, Elfi; Saputra, Yosep Adi; Hanafi, Imam (Al-Hikmah: Jurnal Agama dan Ilmu Pengetahuan, 2025)
Technology in the Society 5.0 era is more focused on the context of humans as superior resources. Competition is prioritized, both in understanding technology, skills, and its implementation in daily activities. Especially for students who must try to win the competition, because job opportunities are limited. Soft skills are a development of Emotional Quotient (EQ), which is part of social intelligence that includes the ability to monitor social emotions and the abilities of others. The opportunity to gain knowledge in a short time in the 2023 MOSMA scholarship program is expected to be able to shape they character after completing the programs and readiness to face the challenges of the sustainable world of work. This research was conducted using survey techniques and qualitative descriptive methods. The data collection method was through in-depth interviews with key informants, namely students receiving the 2023 MOSMA Scholarship from the Ministry of Religion of the Republic of Indonesia. The results of this study include active learning methods that can provide benefits for students to easily understand teaching objectives and be more independent, interactive with teachers, interesting with media and visualizations, easy to evaluate, students as agents of change have and instill strong morals through soft skills and want to continue their education to the Masters level, more enthusiastic, motivated to googling to get educational scholarships and very independent.